Ethnographic Peace Research Approaches and Tensions (Rethinking Peace and Conflict Studies, 2018)
'Peace research has been under-going an "ethnographic turn" whereby peace researchers are increasingly influenced by anthropology - as well as sociology and feminist studies. Gearoid Millar has put together a magnificent line up of authors who have grappled first hand with the ethical and practical challenges of field research. This is a must-have companion for everyone about to embark on field research, and underscores the importance of putting people - and their experiences - at the heart of our research.' Roger Mac Ginty, Professor of Peace and Conflict Studies, University of Manchester, UK 'This is an important book that elaborates an approach to studying conflict that puts those who experience conflict at the centre. Ethnographic peace research is based on the premise that we can only understand conflict or peace through the lived experience of those who are there. This book is a timely antidote to approaches that remove the study of actual people from research, whilst developing a convincing argument that mixed approaches incorporating ethnography can provide a sufficiently accurate understanding of violence and how it can be overcome.' Paul Jackson, Professor of African Politics, University of Birmingham, UK This volume calls for an empirical extension of the "local turn" within peace research. Building on insights from conflict transformation, gender studies, critical International Relations and Anthropology, the contributions critique existing peace research methods as affirming unequal power, marginalizing local communities, and stripping the peace kept of substantive agency and voice. By incorporating scholars from these various fields the volume pushes for more locally grounded, ethnographic and potentially participatory approaches. While recognizing that any Ethnographic Peace Research (EPR) agenda must incorporate a variety of methodologies, the volume nonetheless paves a clear path for the much needed empirical turn within the local turn literature. Gearoid Millar is a Senior Lecturer (Associate Professor) of Sociology at the Institute for Conflict, Transition, and Peace Research (ICTPR), University of Aberdeen. .